DETERMINATION OF THE OPTIMAL CONTENT OF METAL-BURDEN FOR DIFFERENT GRADE MIX OF STEELS, MELTED IN THE STEEL-MAKING FURNACES NO 3 RUP “BELORUSSIAN METALLURGICAL WORKS” - N. V. Andrianov; A. G. Afanasiadi; I. L. Numeranova; A. V. Demin; N. L. Mandel; D. K. Gribok; O. N. Tyscchenko (Литьë и металлургия)
The program ''Calculation of the optimal metalburden composition" allowing to minimize the total cost of charging and of addition elements at the required output of molten metal of the predetermined chemical composition, has been developed on the basis of the offered technology.